Comparative study of in vitro antibacterial activity of eugenia caryophyllus alcoholic extracts and aqueous extracts against different bacteria / Nur Hayani Muhammad Pudzilah - Muhammad Pudzilah, Nur Hayani (2017)
Nowadays, bacteria were more resistant towards antibiotic and antiseptic due to increasing use of drugs, this situation causes worry and limit the preventive measure that decreasing the efficiency of conventional medicine. Therefore, it is crucial to continue searching for new antibacterial agents from natural sources such as medicinal plants. Clove or its botanical name (Eugenia caryophyllus) is one of the medicinal plant or spices that can be proven as effective antibacterial agent. The alcoholic and aqueous extracts of Eugenia caryophyllus shows good activity against Staphylococcus aureus, Serratia sp., Shigella sp., Proteus sp. and E. coli at various concentrations of 100%, 75%, 50% and 25% using disc diffusion method. Alcoholic extract was greatly dominant on aqueous extract in inhibiting the tested bacteria. For phytochemical screening, the results for both of extracts have showed presence of flavonoid, sterols, saponins and reducing components except for aqueous extracts, it showed absence of saponins. As conclusion, according to the good efficacy of Eugenia caryophyllus extracts on the tested microorganisms, it has antibacterial effects and could be used as a therapeutic agent and therefore, it appears to be a potent antibacterial agents that could be considered as a medicinal plant. However, further studies, including identification and purification of the active compounds, will need to be pursued.